Spatio-temporal immunolocalization of VEGF-A, Runx2, and osterix during the early steps of intramembranous ossification of the alveolar process in rat embryos - da Silva Sasso, Gisela Rodrigues; Florencio-Silva, Rinaldo; Sasso-Cerri, Estela [UNESP]; Gil, Cristiane Damas; de Jesus Simões, Manuel; Cerri, Paulo Sérgio [UNESP] (Elsevier, 2021)
Vascular endothelial growth factor A (VEGF-A) is expressed by several cell types and is a crucial factor for angiogenic-osteogenic coupling. However, the immunolocalization of VEGF-A during the early stages of the alveolar process formation remains underexplored. Thus, we analyzed the spatio-temporal immunolocalization of VEGF-A and its relationship with Runt-related transcription factor 2 (Runx2) and osterix (Osx) during the early steps of intramembranous ossification of the alveolar process in rat embryos. Embryo heads (E) of 16, 18 and 20-day-old rats were processed for paraffin embedding. Histomorphometry and immunohistochemistry to detect VEGF-A, Runx2, and Osx (osteoblast differentiation markers) were performed. The volume density of bone tissue including bone cells and blood vessels increased significantly in E18 and E20. Cells showing high VEGF-A immunoreactivity were initially observed within a perivascular niche in the ectomesenchyme; afterwards, these cells were diffusely located near bone formation sites. Runx2-and Osx-immunopositive cells were observed in corresponded regions of cells showing strong VEGF-A immunoreactivity. Although these immunostained cells were observed in all specimens, this immunolocalization pattern was more evident in E16 specimens and gradually decreased in E18 and E20 specimens. Double immunofluorescence labelling showed intracellular co-localization of Osx and VEGF-A in cells surrounding the developing alveolar process, indicating a crucial role of VEGF-A in osteoblast differentiation. Our results showed VEGF-A immunoexpression in osteoblasts and its precursors during the maxillary alveolar process formation of rat embryos. Moreover, the VEGF-A-positive cells located within a perivascular niche at the early stages of the alveolar process development suggest a crosstalk between endothelium and ectomesenchymal cells, reinforcing the angiogenic-osteogenic coupling in this process.
Keywords: Alveolar process; Intramembranous ossification; Osterix; Rat embryo; Runx2; VEGF-A